A comparative study of storm surge and wave setup in the East China Sea between two severe weather events. (5th April 2020) - Wang, Kai; Hou, Yijun; Li, Shuiqing; Du, Mei; Chen, Jinrui; Lu, Jiuyou
Abstract: The coastal regions of the East China Sea are frequently threatened by the increased sea level induced by intense tropical cyclones. In this study, a coupled wave-circulation model ADCIRC + SWAN is used to investigate the spatial and temporal characteristics of storm surges and wave setup heights in the southeastern coastal area of China during two severe weather events with different tracks: Typhoon Saomai, which made direct landfall, and the bypassing Typhoon Chan-hom. By definition, the storm surge is attributable to the wind forcing, while the wave setup results from the wave radiation stress. The simulated sea levels agree well with the observations, with improved results when the wave setup was considered. The simulation results showed clearly different spatial patterns depending on the track type. The maximum storm surge resulted from the cumulative effect of the local onshore wind forcing, occurring on the right side of the Typhoon Saomai track and the left side of the Typhoon Chan-hom track. Significant surge levels along the coast on the left side of the typhoon track were well observed in both cases, resulting from the coastal-trapped shelf waves. The Saomai track type is more likely to cause extremely high storm surges along the coast due to the stronger cumulative effect of the onshore wind forcing. The maximum wave setup was governed by the swell and slope of the sea floor. The locations of the maximum wave setup and surge level were spatially close during Typhoon Saomai, but they were separated during Typhoon Chan-hom. Highlights: The spatial distribution of storm surge strongly depends on the typhoon track. A coastal trapped shelf wave was generated consistently by the alongshore wind. The wave setup was governed by the swell and sea floor slope in the surf zone.